ENLIGHTENMENT AND THE EDUCATION OF A DEVELOPED GENERATION IN THE ACTIVITIES OF THE JADIDS - Xusanov Jahongir Abdimo’minovich; Xasanova Zarrina Shadiyarovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article provides information about the activities of the Jadids and their views on the education of a harmoniously developed generation.